Age-related features of the pattern of oral fluid patients with non-alcoholic fatty liver disease - Nataliya Emelyanova; Dmitry Emelyanov (Folia Medica)
Introduction: In recent years, non-invasive screening methods for diagnosing various human conditions, including those corresponding to biological age, have attracted great interest, one of the sources for non-invasive research of which is oral fluid. Aims: To study the age-related features of oral fluid facies in patients with non-alcoholic fatty liver disease. Materials and methods: Sixty-one patients with non-alcoholic fatty liver disease and 57 somatically healthy patients were selected for study. An oral fluid sample was taken into a plastic tube in the quantity of 1.5-2 ml. The supernatant fluid was collected using a laboratory pipette, and 4 drops of 0.02 ml were formed on a glass slide. After that, the drop was subjected to natural dehydration. The facies study has been carried out using an electron microscope. Results: Normally, during the phase OF drop transition, the formation of 2 zones is characteristic – the marginal zone having the “colloidal glass” form, and the central organized by crystals in the “fern leaf” or “tree branch” form. The metabolic dysfunction negatively affect the organization of protein molecules and the formation of marginal zone in which pathology markers are spread – fissures, wrinkles, pigment inclusions. Conclusion: Accordingly, elements of crystal destruction appear in the salt part, and the number of chaotically oriented dendrites increases.